Students’ Perception of the PMM 4 Program at Universitas Pendidikan Ganesha Bali - Eunika, Astrid; Mashuri, Mashuri; Wahyudin, Wahyudin; Darmawan, Darmawan (Journal of English Language and Education, 2025)
This study investigates students’ perceptions of the Pertukaran Mahasiswa Merdeka (PMM) 4 Program at Universitas Pendidikan Ganesha (Undiksha) Bali. The research aims to explore how participants perceive the academic, cultural, and personal dimensions of their experience during the exchange, including the benefits, challenges, and transformative impacts encountered throughout the program. Employing a qualitative descriptive approach, data were collected through in-depth interviews with four PMM 4 alumni from various Indonesian universities. The findings reveal that students hold predominantly positive perceptions of the program. Academically, PMM 4 enriched their learning experiences through exposure to diverse teaching methods, interdisciplinary courses, and active classroom engagement, which enhanced critical thinking and communication skills. Culturally, the program fostered intercultural awareness and appreciation of Indonesia’s pluralism, enabling participants to develop tolerance and empathy through direct immersion in Balinese traditions. Personally, students reported notable growth in confidence, adaptability, and independence while navigating new academic and social environments. However, several challenges were also identified, including differences in teaching styles, limited coordination between host and home institutions, and workload intensity. Despite these issues, PMM 4 was perceived as a holistic learning platform that integrates academic development with cultural and personal growth, effectively preparing students to engage in a globalized educational context. The study suggests that stronger institutional collaboration, improved mentoring systems, and balanced program design will further enhance the effectiveness and sustainability of PMM in the future.